Effect of a Video-Assisted Teaching Program for Kegel's Exercises on Women's Knowledge About Urinary Incontinence. Issue 5 (September 2015) - Seshan, Vidya; Muliira, Joshua Kanaabi
Abstract : PURPOSE: The aim of this study was to assess community-dwelling women's knowledge about urinary incontinence (UI) and the effectiveness of a Video Assisted Teaching Program for Kegel's Exercises (VATPKE) in increasing their knowledge. METHODS: A cross-sectional design was used to collect data from 598 community-dwelling women. A pre-/posttest design was then used to assess the effectiveness of the VATPKE in improving knowledge about UI in women with self-reported UI (202) and without UI (396). Data were analyzed using independent and paired t tests. RESULTS: Of the 598 participants, 33.8% self-reported having UI. The majority of women with UI (90%) and without UI (90%) had inadequate knowledge. The mean post-VATPKE knowledge levels of women with and without UI were higher than pre-VATPKE mean scores. Differences in knowledge levels in women with and without UI were statistically significant ( P < .001). CONCLUSION: Most of the women at risk or already affected with UI have inadequate knowledge about the condition. In a resource-poor setting with limited health care human resources to provide one-on-one health education, interventions such as the VATPKE may help improve knowledge about UI among the large numbers of affected and at-risk women.